Thresholds of external flows in financial development for environmental sustainability in sub-Saharan Africa - Simplice Asongu; Barbara D. Mensah; Judith Ngoungou (African Governance and Development Institute (AGDI), 2022)
The study complements extant literature by assessing linkages between financial development, external flows and CO2 emissions in 27 sub-Saharan African countries for the period 2002 to 2018. The empirical evidence is based on interactive quantile regressions and external flows consist of remittances, foreign aid, trade openness and foreign investment. The findings establish minimum thresholds of external flows that are needed for the corresponding external flows to interact with financial development in view of promoting environmental sustainability by means of reducing CO2 emissions.
Keywords: C52; O38; O40; O55; P37; 330; foreign aid; remittances; foreign direct investment; official development assistance; trade; CO2 emissions; quantile regressions